Schwannoma in the Posterior Hard Palate and Anterior Mandibular Gingiva: a report of two cases - Samira Basir Shabestari; Iman Shirinbak; Shadi Saghafi-khadem; Nosratolah Eshghyar (Journal of Kerman University of Medical Sciences, 2018)
Background: Schwannoma is a benign tumor which usually presents as a solitary slow-growing painless mass. Approximately 25–48% of all schwannomas occurs in the head and neck region and is found rarely in oral cavity, about 1% of head and neck cases. Tongue is the most common site, followed by buccal mucosa, palate, floor of the mouth, jaw, gingiva and lips. This tumor may present at any age but it is more prevalent in third and fourth decades of life. Case Presentation: Herein we report two cases of schwannoma in a 16-year-old woman and an 18-year-old man with asymptomatic pedunculated mass on anterior mandibular gingiva and painful swelling on posterolateral region of hard palate, respectively. The first lesion was discovered during the routine dental visit and the second one was referred by a dentist. They were medically healthy and their dental radiographies showed no particular findings. The provisional diagnosis for the first and second case was benign mesenchymal lesions and salivary gland tumor, respectively. Excisional biopsy was performed for them. Based on histopathological reports, the definitive diagnosis was neurilemmoma. There was no sign of recurrence approximately 2 years following surgical excision of tumors. The purpose of this report is to present two cases of schwannoma in an unusual location for intraoral tumors. Conclusion: Because of difficulty to diagnose this tumor based on clinical appearance alone, it is suggested that in well-defined peripheral intraoral lesion, schwannoma should be included in differential diagnosis even on palatal or gingival mucosa of young patients. Definitive diagnosis is best stablished by histopathological examination.